Extrarenal calyces associated with pelviureteric junction obstruction: A case report of a rare anomaly - B V Raghunath; M Narendra Babu; B C Gowrishankar; S Ramesh (Wolters Kluwer Medknow Publications, 2012)
Extrarenal calyces are one of the rare renal anomalies associated with the collecting system. Their association with renal ectopia or horse shoe kidney is known. But, here in, we are reporting an intraoperative surprise, where extrarenal calyces were associated with pelviureteric junction obstruction and routine preoperative imaging did not show any light on the diagnosis.